The fidelity of comparison intervention in manual therapy trial for patients with low back pain: a systematic review. (3rd September 2019) - Snow, Mackenzie; Trexler, Sean; Gates, Christine; Pudoka, Kathryn; Wilhelm, Mark
Abstract: Background: Comparison interventions for low back pain are described in the literature utilizing different treatment interventions with various terminology. The effectiveness of these comparison groups is not well defined. Objectives: The objective of this systematic review is to assess the fidelity of comparison interventions within randomized controlled trials assessing the effect of manual therapy on low back pain. Methods: This systematic review utilized PubMed, CINAHL, Scopus, Cochrane, and Pedro databases. Articles were screened by two authors for eligibility criteria and then extracted, reviewed, and cross-checked for data that included sample size, patient demographics, manual therapy intervention, the control group protocol, and outcomes. The Cochrane Risk of Bias tool was used to determine disagreement among authors. A qualitative synthesis of the evidence was completed. Results: A total of 20 articles were included in this systematic review. The comparison interventions were categorized into themes based on the terminology used by the various studies. The themes consisted of "standard care", "sham treatment", "control groups", and unnamed comparison interventions. These themes were then compared to the CPG based on the interventions utilized in each study. Conclusions: There appears to be significant variability in comparison interventions within randomized controlled trials assessing manual therapy effects on patients with low back pain. This variability may lead to inconsistent published effect sizes. It is imperative to correctly follow evidence-based practice from resources, such as the CPG, to determine the effectiveness of treatment interventions.